Semantic Meanderings of Queen in Lexicographic Perspective - Stachurska, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
A lexeme typically conveys a variety of senses. This depends on its actual semantic structure, involves presupposed meanings as well as embraces conversational and situational implicatures. The meaning of a lexeme is also determinated by the context, the situation of its use and the knowledge of the user of a particular language. Hence, the information provided by a particular work of reference is twofold in its nature - semantic and pragmatic. Accordingly, the main objective of the paper is to investigate the semantics and usage value of the lexical item QUEEN throughout the development of the English language.
Keywords: lexicography; dictionary; label; usage; diasystematic information